Changes of transforming growth factor beta 1 in patients with type 2 diabetes and diabetic nephropathy: A PRISMA-compliant systematic review and meta-analysis. Issue 15 (April 2017) - Qiao, Yong-Chao; Chen, Yin-Ling; Pan, Yan-Hong; Ling, Wei; Tian, Fang; Zhang, Xiao-Xi; Zhao, Hai-Lu
Abstract: Background: The existing evidence indicates increased levels of transforming growth factor beta 1 (TGF-β1) in patients with type 2 diabetes mellitus (T2DM) and those with type 2 diabetic nephropathy (T2DN); yet no meta-analysis displays a reliable result. Here we conducted a meta-analysis to evaluate characteristic changes of TGF-β1 in T2DM and diabetic nephropathy. Methods: A systematic search was conducted for eligible studies, which reported the association of TGF-β1 withT2DM and T2DN patients, in PubMed, Wangfang, Chinese-Cqvip, and China National Knowledge Infrastructure database, from February 1, 1991 to December 15, 2015. The association of serum and urine TGF-β1 in T2DM and T2DN patients should be evaluated in case-control studies. The Newcastle-Ottawa Scale was used to access the quality of the included studies, and pooling data were synthesized as standard mean difference (SMD) and 95% confidence interval (CI). The collected data were synthesized according to Cochrane Handbook for Systematic Reviews criteria. Subgroup analysis was conducted by albuminuria and ethnicity. Regression analysis and sensitivity analysis were used to explore the sources of heterogeneity. Publication bias was judged by the Egger test. Results: Sixty-three case-control studies of 364 T2DM patients (1604 T2DN patients) and 2100 healthy controls were included for meta-analysis. Compared with the controls, the cases had increased TGF-β1 levels in both serum (T2DM: SMD 1.78 μg/L; 95% CI 0.98–2.59, P  < .001; T2DN: SMD 4.70 μg/L, 95% CI 3.55–5.85, P  < .001) and urine samples (T2DM: SMD 1.27 pg/mg.creatinine, 95% CI 0.16–2.38, P  < .001; SMD 1.19 ng/L, 95% CI 0.77–1.62, P  < .001; T2DN: SMD 3.14 pg/mg.creatinine, 95% CI 2.15–4.13, P  < .001; SMD 4.50 ng/L, 95% CI 3.16–5.83, P  < .001). The increase of serum TGF-β1 persisted in patients with either microalbuminuria or macroalbuminuria (all P  < .001) in Chinese and non-Chinese population. High heterogeneity exists in some comparisons and small-sample studies. Conclusions: Patients with T2DM and those with albuminuria, Chinese or non-Chinese, had increased serum and urine TGF-β1 levels.